Application of ecodrainage system in reducing the potential for flooding in the District of Sampang - Fauzan Andikha; Adhi Yuniarto (Sustinere: Journal of Environment and Sustainability, 2017)
The Kamoning River watershed is one of the watersheds in Sampang. Sampang City experiences flooding almost every year due to the overflow of the Kamoning River. One of the main causes of flooding in the city is high rainfall and a lack of rainwater catchment areas in the upper and middle sections of the Kamoning River watershed. To address these issues, a flood discharge reduction system using eco-drainage methods is necessary in the upstream and middle areas of the watershed.This study explored two eco-drainage system scenarios. The first scenario involves land-use changes combined with the creation of retention ponds, while the second scenario combines land-use changes with the construction of infiltration wells. Based on the analysis, the designed flood discharge for a 50-year return period in the Kamoning River basin is 289.361 m3/s. Using the first scenario, the designed flood discharge can be reduced by 199.59 m3/s (31.02%). Meanwhile, the second scenario reduces the discharge by 205.20 m3/s (29.08%).Efforts to reduce flood discharge in Sampang can be most effectively implemented using the first scenario.